Effect of cationization pretreatment on the properties of cationic Eucalyptus micro/nanofibrillated cellulose - Pedrosa, Jorge F. S. (2022)
Micro/nanofibrillated celluloses (M/NFCs) have attracted considerable research interest over the past few decades, with various pretreatments being used to reduce energy consumption and/or increase fibrillation. To date, few studies have considered cationization as a pretreatment for their preparation. In this work, quaternary ammonium groups were attached to cellulose fibers by a direct reaction with 2,3-epoxypropyltrimethylammonium chloride or by a two-step method (periodate oxidation + Girard's reagent T). The cationic fibers with degrees of substitution (DS) between 0.02 and 0.36, were subjected to homogenization treatment. The morphological properties, chemical composition, and rheological behavior were evaluated to assess the effect of DS and the effect of the cationization method (for samples with similar DS). The two-step cationization resulted in significant degradation of the cellulose structure, leading to the formation of short fibrils and solubilization of the material, ranging from 6% to almost complete solubilization at a DS of 0.36. Direct cationization resulted in longer fibrils with an average diameter of 1 μm, and no significant cellulose degradation was observed, leading to a more cohesive gel-like material (at 1 wt%). These observations clearly show the strong influence of the cationization method on the final properties of the cationic cellulosic materials.